Pengelolaan Tanah Pecatu Desa Dengan Sistem Perjanjian Bagi Hasil Di Kecamatan Masbagik Kabupaten Lombok Timur: Studi Di Desa Danger Lombok Timur - Rialdi Isna Falah; Arief Rahman (Fakultas Hukum Universitas Mataram, 2022)
This research has the purpose to find out the mechanism of The Pecatu village land management with a profit-sharing agreement system in Masbagik sub-district, and find out their rights and duties to all parties in the Pecatu village land in Danger Village, Mas Bagik Sub-district have been failed. This research is an empirical legal research method and uses the statutory, sociologica, and conceptual, approach. From this research, the result of this study showed (1) The Pecatu village land management with a profit-sharing agreement system at Masbagik followed the norms in Act Number 2 of 1960 concerning the profit-sharing agreement and not again followed adat law. (2) if in the Pecatu village land has failed in the harvest, the parties are still doing whatever their rights and their duties based on the written agreement they are made, and all their loss in this agreement is a risk for the village government.